Social protection management system in the Altai Republic - E. V. Domashova (Вестник университета, 2021)
The article actualizes the issue of studying the experience of forming an effective management system of social protection of the population of the region. The paper considers the main socio-geographical, natural and climatic features of the region, ethno-cultural features that determine the formation of an effective social protection management system of the republic. The author notes that the underestimation of these features of the formation of the social protection management system in the Altai Republic significantly reduces its effectiveness. The study considers the structural divisions of the Ministry of Labor, Social Development and Employment of the Population of the Altai Republic and subordinate institutions. As a result of the analysis of Internet resources as well as theoretical analysis of the reports of the Ministry of Labor, Social Development and Employment of the Altai Republic, problematic areas of the functioning of the social protection management system of the republic were identified.